Resonance Of Reformist-Modernist Islamic Thought in Interpretation and Its Influence on The Development of Interpretation in Indonesia - Haririe, Muhammad Ruhiyat (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
At the end of the Ottoman rule, Muslims experienced extraordinary setbacks in various fields. This is suspected to be due to several factors, including the difficulty of Muslims in understanding Islam, the spread of an understanding of Islam which seems old-fashioned, and the practice of practicing Islamic teachings which is considered quite deviant. One of the causes of all these causes is that the verses of the Quran that are understood are not in accordance with the context of the times. This research aims to explain interpretations with reformist-modernist nuances in the context of ideology, influence, relevant interpreters, and criticism of traditional Islam. The research method used is qualitative with descriptive analysis based on literature study. The conclusion of this research shows that the development of reformist tafsir emerged as a response to the decline of Muslims in all aspects of life. Reformers such as Jamaluddin Al-Afghani, Muhammad Abduh and Rasyid Rida had a significant influence on the development of tafsir with reformist-modernist nuances. Prominent mufassir in the archipelago who helped develop interpretations with reformist nuances include A. Hassan, Oemar Bakri, Buya Hamka, and KH. Bisri Musthofa..The leaders of the reformist movement also criticized many traditionalists who they considered to prioritize blind taqlid and were exposed to bid'ah and khurafat.